Production of fatty acid methyl ester from waste cooking oil utilizing sulfonated tio2-sio2 catalyst - Kamarullah, Shahida Hanum; Nik Arif Kamilan, Nik Nur Ayunni; Abdullah, Nur Ainun Nazhirah; Mohd Khazaai, Siti Norhafiza (GADING Journal of Science and Technology, 2023)
Biodiesel is a sustainable, renewable, biodegradable, and non-toxic diesel fuel replacement that can easily be synthesized through the esterification reaction. Waste cooking oil (WCO) has been utilized as a feedstock for biodiesel production. However, there is difficulty to convert feedstock into biodiesel using basic catalyst due to high levels of free fatty acid (FFA). Therefore, sulfonated TiO2-SiO2 has been used as a solid acid catalyst via the esterification reaction. The aim of this study is to determine the effect of reaction time and catalyst loading on the production of fatty acid methyl ester (FAME) using sulfonated TiO2- SiO2 catalyst from WCO. Characterization using SEM-EDX confirmed the presence of Ti, Si, O, and S in the catalyst and revealed the rough surface of the impregnated sulfonated TiO2- SiO2. Hammett indicators analysis indicated that the catalyst was in a moderate acidity range. WCO was esterified with methanol using sulfonated TiO2-SiO2 as solid acid catalyst to produce biodiesel. The reactions were refluxed at 90 ºC with 3 wt% catalyst loading and 9:1 methanol to oil ratio while varying the reaction time (1 to 5 h). Meanwhile for the effect of catalyst loading (1 to 5 wt%), the reaction temperature, reaction time and methanol-to-oil ratio were constant at 150 ℃, 2 h, and 15:1, respectively. In this study, it was found that the highest FAME yield obtained from the effect of catalyst loading was 67.07% with optimum conditions of 3 wt% catalyst loading, 15:1 methanol to oil ratio, and a reaction temperature of 150 ºC for 2 h. The gas chromatography-mass spectrometry (GC-MS) results showed that eight peaks corresponding to the methyl ester group were found in the product, indicating that the FFA can be converted to methyl ester using sulfonated TiO2-SiO2 in the esterification reaction.